(untitled) (International Journal of Multidisciplinary Research and Explorer, 2021)
The purpose of this paper to explore the Micro, Small and Medium Enterprises in one of the backward district (Poonch) of Jammu and Kashmir UT. The paper represents the performance of MSMEs and also discussed various problems faced by these units in the district. The paper is prepared after a deep literature review and finding a research gap. It is based on the secondary data collected from the District Industries Center (Poonch). The study is based on thetime series data of 17 years, compound annual growth rate and multiple regression analysis is used to analyse the data. The study found that there is a significant relationship between Employment and Number of Units, Investment and Production. The study also discusses the various problems faced by MSMEs in the study area and also suggests measures to improve it.